Salt stress is regulated by interactions with heat and spatiotemporal changes in rice plants - Mendes, Kellyane da Rocha (2024)
This thesis was developed to test the hypotheses that spatiotemporal variation factors (plant parts and developmental stage) and heat interaction differentially affect the effects of salinity on key physiological growth processes in rice plants. In chapter 1, a review study was developed addressing the importance of these themes in plant physiology in the context of rice growth and productivity. In chapter 2, rice plants were challenged with salinity, with 25 mM NaCl at the beginning of the vegetative phase (V4 stage), and 50 mM from V7 until the final reproductive phase of panicle maturation (R9). The objective was to study the interactions between salinity and reproductive phases in spatial variation (plant parts: flag leaves, middle leaves, roots, culms and panicles). The results indicate that the ontogenetic phases of the leaves (age) significantly affect the negative effects of salinity, with older leaves (basal) being more susceptible to the processes of senescence and cell death induced by salinity. Salinity also severely affects rice productivity, including the number of panicles, mass and number of seeds and harvest index. In addition to significantly affecting the quality of seeds indicated by low germination rate and low vigor. These results were associated with Na+ accumulation and reductions in K+/Na+ ratios in these parts of the plant. Total N contents were also differentially affected in response to plant parts and reproductive stages. The oldest and dead leaves showed low fluctuations in total N content in both stages R3 and R7, while the flag leaves showed a high reduction caused by saline stress, especially in R7. Taken together, the data suggest that leaves were intensely affected by saline stress, exhibiting intense senescence associated with protein degradation. Changes in the profile of free amino acids and other metabolites, as well as multivariate analyzes (PCA, principal component analysis) corroborate the results, indicating that the protein degradation process is intensely stimulated in salt stress and that there is an intense variation spatial (different parts of the plant) and temporal (stages of plant development). That is, the metabolite processes and sensitivity to salt stress in terms of rice growth are spatiotemporally dependent. In chapter 3, a manuscript was developed involving the interactions between heat and salinity in rice plants. We tested the hypothesis that heat can stimulate Na+ transport towards the leaves, aggravating the osmotic and ionic effects. In parallel, the heat-salinity interaction could favor the antioxidant response in rice leaves. Rice plants were previously exposed to 0 and 100 mM NaCl for eight days at 27 °C and subsequently two groups were transferred to high temperature (42 °C) for 10 hours (heat and heat + salt) while two others were transferred to 27 °C (control and salt). The heat-salinity interaction greatly stimulated the accumulation of Na+ in the leaves, causing an intense decrease in the K+/Na+ ratios, inducing significant osmotic and ionic changes. The stomata were closed, causing drastic damage to the assimilation of CO2 and reducing the efficiency of water use. In contrast, PSII activity was less affected. Unexpectedly, this combined stress partially favors oxidative protection, as indicated by the reduction in H2O2 levels and lipid peroxidation associated with the reduction in reduced ascorbate and glutathione contents and increased enzymatic activities. Therefore, high temperature drastically aggravates the negative effects caused by salt stress on photosynthetic efficiency, despite this interaction having partially favored antioxidant defense. Taken together, the work conducted in this thesis reveals that salinity acts on rice plants, and possibly on most species, in an integrative and systemic way, involving multi-environmental and endogenous components, which interact with each other and in a spatial- temporal.